2013
DOI: 10.1152/japplphysiol.00068.2013
|View full text |Cite
|
Sign up to set email alerts
|

The frequency response of cerebral autoregulation

Abstract: The frequency-response of pressure autoregulation is not well delineated; therefore, the optimal frequency of arterial blood pressure (ABP) modulation for measuring autoregulation is unknown. We hypothesized that cerebrovascular autoregulation is band-limited and delineated by a cutoff frequency for which ABP variations induce cerebrovascular reactivity. Neonatal swine (n = 8) were anesthetized using constant minute ventilation while positive end-expiratory pressure (PEEP) was modulated between 6 and 0.75 cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
80
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 23 publications
3
80
0
Order By: Relevance
“…(4) or to the fact that we are measuring local autoregulation at the microcirculation level as opposed to organ-level autoregulation is a subject for future studies. However, we observe that one recent study also reported a low autoreguation cutoff frequency of ~0.03 Hz [28], consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
“…(4) or to the fact that we are measuring local autoregulation at the microcirculation level as opposed to organ-level autoregulation is a subject for future studies. However, we observe that one recent study also reported a low autoreguation cutoff frequency of ~0.03 Hz [28], consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
“…Even though this transfer function analysis description of cerebral autoregulation is common, 3,11,[20][21][22] we are aware of only a few studies that are explicitly based on a high-pass filter analysis involving the concept of autoregulation cutoff frequency. 11,17,35 In this work, we focus on the assessment of autoregulation cutoff frequencies as a measure of the effectiveness of cerebral autoregulation: namely, the higher the cutoff frequency, the better the suppression of CBF oscillations at any frequency, and the better the autoregulation.…”
Section: Hemodynamic Modelmentioning
confidence: 99%
“…When we arrived home, we programmed our computers, running ICM (intensive care monitor) software [7], to calculate a moving correlation coefficient from 30 consecutive 10-s averages of ICP and ABP waveforms. We called this the PRx index (pressure reactivity index) [6].The rationale for averaging ICP and ABP waveforms over 10 s was that only slow waves, of frequencies lower than 0.05 Hz, can carry information about autoregulation [11]. Simple averaging is a sufficient method of filtration of all faster components (mainly respiratory and pulsatile), which do not contain or contain only a little of any autoregulationrelated signatures.…”
mentioning
confidence: 99%
“…The rationale for averaging ICP and ABP waveforms over 10 s was that only slow waves, of frequencies lower than 0.05 Hz, can carry information about autoregulation [11]. Simple averaging is a sufficient method of filtration of all faster components (mainly respiratory and pulsatile), which do not contain or contain only a little of any autoregulationrelated signatures.…”
mentioning
confidence: 99%